Blurring the Lines: An Analysis of Jurisdictional Overlap between General Courts and State Administrative Courts in Indonesia - Ayesha Hanum Nurrahmah; Fithriyatirrizqoh; Moh Imam Gusthomi (Arkus, 2025)
The Indonesian legal system adopts a dual court system, comprising General Courts and State Administrative Courts (PTUN), each with distinct jurisdictions. However, ambiguities arise when State Administrative Decisions (TUN) involve elements of civil law, leading to jurisdictional overlaps and potential conflicts between these courts. This overlap creates confusion and uncertainty for litigants seeking legal recourse. This study employed a qualitative legal research methodology, involving a comprehensive analysis of relevant legislation, including Law No. 5 of 1986 on State Administrative Courts, Law No. 48 of 2009 concerning Judicial Power, and related regulations. Additionally, the study examined relevant case law from both General Courts and the PTUN, spanning from 2018 to 2024, to identify patterns and trends in jurisdictional disputes. The research identified recurring areas of jurisdictional overlap, particularly in cases involving land disputes, contractual disputes with government entities, and disputes arising from the execution of TUN decisions. Analysis of case law revealed inconsistencies and contradictions in how courts have resolved these overlaps, leading to legal uncertainty for litigants. In conclusion, the jurisdictional overlap between General Courts and the PTUN presents a significant challenge to the Indonesian legal system, undermining legal certainty and access to justice. This study proposes potential solutions, including clearer legislative guidelines, enhanced judicial training, and the establishment of a dedicated mechanism for resolving jurisdictional conflicts.